2014
DOI: 10.1159/000358716
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin Accentuates the Anti-Tumor Effects of Photodynamic Therapy via Inactivation of NF-κB in Eca109 and Ec9706 Esophageal Cancer Cells

Abstract: Background: Photodynamic therapy (PDT) is a new treatment for esophageal cancer which has been shown to be effective in the elimination of tumor. However, PDT could induce the activation of nuclear factor-kappa B (NF-κB) in many photosensitizers based PDT, which plays a negative role in PDT. In addition, our previous results have shown that dihydroartemisinin (DHA), which was the most potent one of artemisinin derivatives, has anticancer activity in esophageal cancer cells. Methods: Cell viability was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…In addition to its potent anti-malarial activity, emerging studies have shown that DHA may also be a potential chemopreventive drug, exhibiting strong antitumor activity in various human cancer cells by blocking cell proliferation [5], arresting cell cycle [6], promoting apoptosis [7], and inhibiting angiogenesis and metastasis [8, 9]. In addition, DHA can potentiate the anticancer effect of chemotherapeutic agents and photodynamic therapy to induce cell apoptosis in various kinds of cancers [10-13]. Curcumin (Cur) is a well-known dietary polyphenol extracted from the rhizome of the plant Curcuma longa .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its potent anti-malarial activity, emerging studies have shown that DHA may also be a potential chemopreventive drug, exhibiting strong antitumor activity in various human cancer cells by blocking cell proliferation [5], arresting cell cycle [6], promoting apoptosis [7], and inhibiting angiogenesis and metastasis [8, 9]. In addition, DHA can potentiate the anticancer effect of chemotherapeutic agents and photodynamic therapy to induce cell apoptosis in various kinds of cancers [10-13]. Curcumin (Cur) is a well-known dietary polyphenol extracted from the rhizome of the plant Curcuma longa .…”
Section: Introductionmentioning
confidence: 99%
“…Dihydroartemisinin (DHA), the major active metabolite of artemisinin, has been found to inhibit the growth of cancer cells in a variety of cancers (12)(13)(14)(15). Xie et al (16) reported that the concentration of DHA was two-fold higher in the brain than in the plasma, which indicates that DHA is able to penetrate the brain-blood barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer is an aggressive malignancy associated with a poor prognosis, and the 5-year survival rate of ESCC patients is approximately 19% [22,23]. The high mortality rate of ESCC can be partly attributed to the fact that it is typically diagnosed at an advanced stage, underscoring the need to identify biomarkers for the early detection of this disease.…”
Section: Discussionmentioning
confidence: 99%